# Example 3 - Chapter 13 Class 11 Limits and Derivatives

Last updated at Sept. 17, 2019 by Teachoo

Last updated at Sept. 17, 2019 by Teachoo

Transcript

Example 3 Evaluate: (i) lim (x 1) (x 15 1)/(x10 1) lim (x 1) (x 15 1)/(x10 1) = ( (1) ^15 1)/( (1) ^10 1) = (1 1)/(1 1) = 0/0 Since it is form 0/0, we can solve by using theorem lim (x a) ( ^ ^ )/( ) = na n 1 Hence, lim (x 1) ( ^15 1)/( ^10 1) = lim (x 1) ^15 1 lim (x 1) x10 1 = lim (z 1) ^15 (1) ^15 lim (z 1) x10 (1)10 Multiplying and dividing by x 1 = lim (z 1) ( ^15 1^15)/( 1) lim (z 1) ( ^10 (10) ^10)/( 1) Comparing lim (x 1) (x^15 (1) ^15)/(x 1) with lim (x a) (xn an)/(x a) = nan 1 Here a = 1 , n = 15 , x = x lim (x 1) ( ^15 (10) ^15)/( 1) = 15(1)15 1 = 15 (1)14 = 15 Also comparing lim (x 1) (x^10 (1) ^10)/(x 1) with lim (x a) (x^n a^n)/(x a) Here x = x , n = 10 , a = 1 So, lim (z 1) ( ^10 (1) ^10)/( 1) = (10) (1) 10 1 = (10) (1)9 = 10 Hence , = lim (x 1) ( ^15 1^15)/( 1) lim (x 1) ( ^10 110)/( 1) = 15 10 = 15/10 = 3/2 ( ) ( ) ( ^ )/( ^ ) = / Example, 3 Evaluate: (ii) lim (x 0) ( (1 + x) 1)/x lim (x 0) ( (1 + x ) 1)/x Putting x = 0 = ( (1 + 0) 1)/0 = ( (1 ) 1)/0 = (1 1)/0 = 0/0 Since it is a 0/0 form We simplify the equation Putting y = 1 + x y 1 = x As x 0 y 1 + 0 y 1 So, our equation becomes lim (x 0) ( (1 + x ) 1)/x = lim (x 1) ( ( y ) 1)/(y 1) = lim (x 1) ( ( ) ^(1/2) 1)/(y 1) = lim (x 1) ( ( ) ^(1/2) (1) ^(1/2))/(y 1) = 1/2 (1) ^(1/2 1) = 1/2 (1) ^(1/2) = /

Examples

Example 1

Example 2 Important

Example 3 Important You are here

Example 4

Example 5

Example 6

Example 7

Example 8

Example 9

Example 10

Example 11

Example 12

Example 13

Example 14

Example 15

Example 16

Example 17 Important

Example 18

Example 19 Important

Example 20 Important

Example 21 Important

Example 22 Important

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.